Variant expression dziesiąta, dziewiąta, siódma, piąta etc. woda na, po kisielu in dictionaries and texts - Ignatowicz-Skowrońska, Jolanta (Papers in Linguistics, 2023)
The research on the title expression was inspired by its semantic actualizations which come unnoted in majority of latest language dictionaries but are found in contemporary texts. The objective was to prove the thesis that in the contemporary Polish language the unit expands its real reference and takes on new meanings – this was done by the analysis of its notation in lexicographical collections and its use in old and contemporary Polish. The findings show that the title unit has had two shades of meaning – ‘very distant relative’ and ‘loose relationship of something with something’. The latter has been inconsistently noted in dictionaries, exemplified by one quote only and has not entered majority of lexicographical collections. The research proved also that the expression was subject to various modifications which made it a multiform unit whose components undergo semantization in certain actualizations. Certain formal transformations of the unit, namely the alternation of isomorphic components and prepositions like the change of preposition ‘na’ for preposition ‘po’ (… woda na kisielu → … woda po kisielu) facilitated the arising of new motivation of the phraseological unit which appeared in Polish as a borrowing.